Digital Fabrication Technology in Concrete Architecture - Pedro Carvalho (2014)
Technological innovation has been an important driving force in architecture, enabling and inspiring architects and engineers by giving them new tools for solving existing problems. In the last two decades, the exploration of digital design and fabrication technologies has stimulated the development of a variety of interests and strategies to materialize increasingly complex and customized solutions in architecture, with traditional building materials. Reinforced concrete is the most widely used material in the building industry today and throughout its history has been the subject of vast research into its performance as a construction material and its tectonic potential in architecture. As such, the introduction of digital fabrication processes in concrete construction represents the biggest prospect for renovation of our built environment and at the same time, presents particular difficulties and opportunities, which are now being addressed. In an effort to investigate the alternative design and material possibilities in concrete emerging from the use of digital fabrication technologies in architecture, this paper proposes a focused view of digital fabrication applied to concrete construction with two areas of research. By framing the research in the context of reference works in concrete architecture of the 20th century, this paper describes and illustrates taxonomy of existing and possible types of integration of digital fabrication technologies in concrete architecture in the realms of Practice and Research. This characterization allows the authors to frame the relation between material, technology and architecture in different environments regarding the same material, extracting a clear image of existing processes, their potential and shortcomings, as well as expectations for future developments.